Pengaruh Quality of Work Life dan Knowledge Management terhadap Organizational Citizenship Behavior (OCB) pada Pegawai Bank Nagari Simpang Empat - Helli Fransisca; Suhelmi Helia (YASIN, 2026)
Excellent and high-quality human resources are an important factor in supporting the achievement of organizational goals, including in the banking sector, which requires employees to work professionally and demonstrate voluntary work behavior beyond their formal duties. This study aimed to analyze the effect of quality of work life and knowledge management on the organizational citizenship behavior (OCB) of employees at Bank Nagari Simpang Empat Branch. This study used a quantitative approach with a survey design. The research population included all 84 employees of Bank Nagari Simpang Empat Branch, consisting of 53 permanent employees and 31 outsourced employees. The sampling technique used was total sampling, so the entire population was included as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25.0. The results showed that quality of work life had a positive and significant effect on OCB. Knowledge management also had a positive and significant effect on OCB. Simultaneously, the two variables had a positive and significant effect on employees’ OCB. These findings confirm that improving the quality of work life and knowledge management plays an important role in encouraging employees’ voluntary work behavior. The implications of this study indicate the need for banking organizations to strengthen a work environment that supports employee well-being and optimize knowledge management as a human resource development strategy oriented toward improving organizational performance.